2020
DOI: 10.1038/s41467-020-19803-9
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal FGF15/19 physiologically repress hepatic lipogenesis in the late fed-state by activating SHP and DNMT3A

Abstract: Hepatic lipogenesis is normally tightly regulated but is aberrantly elevated in obesity. Fibroblast Growth Factor-15/19 (mouse FGF15, human FGF19) are bile acid-induced late fed-state gut hormones that decrease hepatic lipid levels by unclear mechanisms. We show that FGF15/19 and FGF15/19-activated Small Heterodimer Partner (SHP/NR0B2) have a role in transcriptional repression of lipogenesis. Comparative genomic analyses reveal that most of the SHP cistrome, including lipogenic genes repressed by FGF19, have o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 56 publications
4
42
1
Order By: Relevance
“…Furthermore, fibroblast growth factor-15/19 is a bile acid-induced gut hormone in the late fed phase that acts to decrease hepatic lipogenesis. Fibroblast growth factor-15/19 suppresses hepatic lipogenesis through an epigenetic mechanism by activating its downstream nuclear receptor small heterodimer partner, which in turn recruits the DNA methyltransferase DNA methyltransferase-3a to lipogenic gene loci such as fatty acid synthase ( Kim Y. C. et al, 2020 ). This study may shed new light on protection against metabolic diseases.…”
Section: Gm and Metabolic Diseasesmentioning
confidence: 99%
“…Furthermore, fibroblast growth factor-15/19 is a bile acid-induced gut hormone in the late fed phase that acts to decrease hepatic lipogenesis. Fibroblast growth factor-15/19 suppresses hepatic lipogenesis through an epigenetic mechanism by activating its downstream nuclear receptor small heterodimer partner, which in turn recruits the DNA methyltransferase DNA methyltransferase-3a to lipogenic gene loci such as fatty acid synthase ( Kim Y. C. et al, 2020 ). This study may shed new light on protection against metabolic diseases.…”
Section: Gm and Metabolic Diseasesmentioning
confidence: 99%
“…SHP knockout mice show decreased expression of genes involved in lipogenesis (PPAR γ and ACC) and increased expression of genes involved in lipid oxidation and export (PPAR α and VLDL) [ 256 ]. A new study reported that SHP overexpression in mice inhibits lipogenesis in a DNA methyltransferase-3a- (DNMT3A-) dependent manner [ 257 ]. Moreover, SHP expression is regulated by other NRs in livers.…”
Section: Transcriptional Regulation Of Lipid Metabolism By Nrs In Nafldmentioning
confidence: 99%
“…This is the case of aldafermin (NGM282), a drug that shows positive results in the treatment of liver diseases as non-alcoholic steatohepatitis (NASH) [130] or primary sclerosing cholangitis [131]. Other studies support the idea that FGF15 could be used as a potential therapeutic option in other liver diseases [132,133]. Studies reported by our group indicated that a single dose of FGF15 in BD and cardiac death (CD) donors promote less damage and regenerative failure in liver grafts without observing hepatic tumor signals [20,21].…”
Section: Non-protumorigenic Variants Of Fgf15/19mentioning
confidence: 99%